Applying Brown’s double exponential smoothing technique to forecast HIV prevalence among people aged 15-49 years in Belize (Texas Journal of Medical Science, 2024)
This study uses annual time series data on HIV prevalence among people aged 15-49 years for Belize from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes double (Brown) exponential smoothing model. The optimal value of the smoothing constant α is 0.7 based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15- 49 years will continue to decline over the out of sample period. Therefore, we encourage policy-makers to strengthen HIV case detection, behavioral change interventions and other HIV prevention measures especially among key populations